An evaluation of foundation doctor training : a mixed-methods study of the impact on workforce well-being and patient care [the Evaluating the Impact of Doctors in Training (EDiT) study] /: a mixed-methods study of the impact on workforce well-being and patient care [the Evaluating the Impact of Doctors in Training (EDiT) study]. (December 2013) - Mason, Suzanne
No abstract available